Family care reduces the incidence of neonatal sepsis: A systematic review and meta-analysis - Ganji, Niloofar; Alganabi, Mashriq; Yamoto, Masaya; Chusilp, Sinobol; Pierro, Agostino; Li, Bo (Frontiers in Pediatrics, 2023)
Purpose: Family-involved care in the neonatal intensive care unit (NICU) helps to alleviate neonatal anxiety and promotes breastmilk intake, body growth and neurological development, but its effect on reducing the incidence of neonatal sepsis is not known. We conducted a systematic review and meta-analysis of randomized controlled trials (RCT) to evaluate whether neonates receiving family care have a lower incidence of neonatal sepsis compared to neonates receiving standard NICU care. Methods: MEDLINE, Embase, Web of Science, and CENTRAL were searched for RCTs that compared preterm neonates receiving family care vs. standard NICU care. From 126 articles that were identified and screened, 34 full-text articles were assessed for eligibility, and 5 RCTs were included. The primary outcome was the development of sepsis. The RevMan 5.4 software was used to conduct the Meta-analysis. Results: The metanalysis, based on 5 RCTs demonstrated that neonates receiving family-involved care had significantly lower incidence of sepsis (12.0% vs 16.3%), increased body weight, and reduced length of hospital stay compared to those receiving standard NICU care. Conclusion: This study suggests that family-involved care in NICU can (i) reduce the incidence of neonatal sepsis, (ii) improve growth, and (iii) reduce the length of hospital stay. This study highlights the need for evaluating whether family-involved care improves other neonatal outcomes.